2011
DOI: 10.1097/prs.0b013e31821e6f51
|View full text |Cite
|
Sign up to set email alerts
|

Transversus Abdominis Plane Block Anesthesia in Abdominoplasties

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 11 publications
4
74
0
Order By: Relevance
“…In three studies, the injection of local anesthetic into the TAP was performed from inside the abdominal wall. [16][17][18] The remaining 12 studies used a non-US-guided loss-ofresistance technique. Tables 2 and 3 provide a summary of the statistical analysis (i.e., mean VAS differences, CI, P value, heterogeneity scores, and quality of the evidence [GRADE]) for each of the subcategories of TAP block use described below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In three studies, the injection of local anesthetic into the TAP was performed from inside the abdominal wall. [16][17][18] The remaining 12 studies used a non-US-guided loss-ofresistance technique. Tables 2 and 3 provide a summary of the statistical analysis (i.e., mean VAS differences, CI, P value, heterogeneity scores, and quality of the evidence [GRADE]) for each of the subcategories of TAP block use described below.…”
Section: Resultsmentioning
confidence: 99%
“…Pain scores at six and 12 hr were investigated in 23 and 18 [16][17][18][19][20][21][22][23]25,26,29,31,32,[34][35][36][38][39][40][41] studies, respectively. The overall analyses showed that, in the TAP block group, the six-hour VAS pain score was reduced by 1.4 (95% CI, -1.9 to -0.8; P \ 0.001) (Fig.…”
Section: Transversus Abdominal Plane Block Vs Placebomentioning
confidence: 99%
“…However, the study was limited in that efforts to obtain subjective pain scores from a patient in the immediate recovery period were often impaired by the systemic effects of general anesthesia. Sforza et al 9 also used a similar technique in placing a specific anesthetic block in the transversus abdominis plane. This study was also limited to the immediate postoperative recovery period; more important, that nerve block technique is much more difficult to perform, and there is a significant risk of inadvertent peritoneal puncture.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral nerve blocks - specifically transversus abdominis plane (TAP) blocks - have been described [18-20]. A modification of the TAP technique which involves surgeon placement of the TAP catheters directly into the open surgical wound (medial open transversus abdominis plane; MOTAP) has been investigated both at Sunnybrook Health Sciences Centre and at the University Health Network – Toronto General Division [21].…”
Section: Introductionmentioning
confidence: 99%